A pressure drop prediction model for hydrate slurry based on energy dissipation under turbulent flow condition. (1st March 2022) - Fu, Weiqi; Yu, Jing; Xiao, Yang; Wang, Chenglai; Huang, Bingxiang; Sun, Baojiang
Highlights: A novel pressure drop model for hydrate slurry is developed under turbulent flow based on the energy dissipation. The model analyzes the influences of wall resistance, collisions of hydrate particles, collisions of hydrate particle-wall and the friction of carry liquid-hydrate particle on pressure drops. The wall resistance contributes about 49% to 64% of pressure losses. The collisions of hydrate particles contribute about 35% to 49% of pressure losses. The total energy dissipations induced by the others only contribute within 0.2%. Abstract: In the development of natural gas hydrates (NGHs) in deep-water environment, gas hydrates will form in the water-drainage line of the wellbore due to low-temperature and high-pressure environment. The flow pattern in the water drainage line is hydrate slurry bubbly flow (HSBF). Thinking that no proper model has been built yet, a novel model is proposed for predicting the pressure drop of HSBF based on the energy dissipation theory. The model considers the influences of the wall resistance, the collision of hydrate particles, the collision of hydrate particle-pipe wall and the friction of carry liquid-hydrate particle on the energy dissipation caused by hydrate slurry flowing. The wall resistance and the collision of hydrate particles are main reasons inducing the pressure drop during hydrate slurry flowing under turbulent flow, which their contributions to the total energy dissipations are from 49% to 64% and from 35% to 49% correspondingly with hydrate concentrations increasing. The sum of energy dissipations for the other two factors are only within 1.35%. The reliability of the proposed model is validated by the published data. Most of discrepancies are within ±10% and all discrepancies are less than ±20%.